Relação entre traços de personalidade, percepção de justiça distributiva, satisfação e comportamentos contraproducentes no trabalho - Monica Freitas Ferreira (2013)
This study had the objective of verifying possible relations among the dimensions of personality, job satisfaction and the perception of distributive justice of workers with the occurrence of counterproductive workplace behaviours (CWB). 381 workers participated in this study with 142 of them being residents of cities of the Minas Gerais State Brazil and 239 from cities of the Bahia State Brazil. They had different educational and socioeconomic statuses, the majority completed high school (35,4%), followed by those with post graduate studies (34,1%), and finally those with higher education (30,2%). The participants were employees from public and private sectors all of them with formal employment relationships for over a year in different divisions of the workplace and hierarchical levels. 74,3% of the total sample were female and the age of the participants varied between 18 and 69 (DP = 8,47; M=30,42). The composition of this sample was carried out through convenience. The size of the companies varied from small (12,0%) to large companies (46,0%). This study used the Workplace Deviance Scale (WDS), the California Psychological Inventory (CPI-Cp), the Job Satisfaction Scale, the Perceived Distributive Justice Scale and the NEO-PI-R. The results showed, generally, correlations of magnitudes considered to be null to moderate amongst different variables. The personality factors: Neuroticism, Amiability, Conscientiousness and the factors of job satisfaction Satisfaction with the nature of the job and promotions presented correlations of moderate magnitude with the counterproductive behaviours. However, the higher the score on Amiability, Conscientiousness and job satisfaction the less involvement of the employees with counterproductive behaviours, while the higher the score on Neuroticism the more involvement with CWBs.